Mexican Acmaeodera Eschscholtz, 1829: A new species and checklist, with miscellaneous taxonomic and biological notes on other North American Buprestidae (Coleoptera) - Davidson, J. M. (Zootaxa, 2003)
Acmaeodera jeanae, sp. nov., is described from Oaxaca in southern Mexico, and is compared with A. scapularis Horn, 1894 from Baja California Sur, Mexico and A. mixteca Westcott, 1998 from Oaxaca and Puebla, Mexico. A checklist of the species of Acmaeodera known from Mexico, including Baja California is provided. Notes describe the predatory behavior of Cerceris grandis Banks (Hymenoptera: Sphecidae) upon Gyascutus planicostus (LeConte), 1858 and predation by Cerceris californica Cresson upon Acmaeodera maculifera Horn, 1894. A new adult host plant is noted for Acmaeodera recticollis Fall, 1899. The genus Squamodera Nelson, 1996, and the four species and synonyms included therein, are transferred to the genus Acmaeodera as a subgenus. Acmaeodera loei Manley, 1987 is recorded from Mexico for the first time.